A study on the effect of reinforcement on the strength of concrete core. (2021) - Lessly, S. Herald; Senthil, R.; Krishnakumar, B.
Abstract: Concrete core test is a semi-destructive test, conducted to ascertain the in- situ strength of the hardened concrete of a structure. In such case it is desired to extract cores without reinforcement. If the reinforcements are present in the core, then the core strength does not mean the compressive strength of concrete in the structure from which the core was extracted. The objective of this study was to study the effect of orientation of reinforcement on the compressive strength of concrete core. 10 mm and 12 mm reinforcement were embedded in the test specimens. A set of cores containing different orientations of reinforcement were extracted. The test results indicate that the presence of reinforcement of diameter 12 mm reduces the strength of concrete core from 3% to 30%, while the reinforcement of diameter 10 mm reduces the strength of concrete core from 5% to 36%. The bond between the reinforcement and the core gets affected during the coring action due to which the strength gets reduced in a reinforced core. The reduction of strength of an unreinforced core ranges around 40% when compared to the cube compressive strength. An empirical relationship with several factors influencing the core compressive strength is formulated and the same is validated.